INOVASI PELAYANAN LAPAK DARLING (LAYANAN PAJAK DAERAH KELILING) DALAM OPTIMALISASI PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI BADAN PENDAPATAN DAERAH KOTA PEKANBARU TAHUN 2024 - Wilda Lativa; Fadhiilatun Nisaa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This research is motivated by the challenges in optimizing the Regional Original Income (PAD) of Pekanbaru City, even though the revenue target has increased, which encourages the Regional Revenue Agency (BAPENDA) of Pekanbaru City to present the service innovation of Lapak Darling (Mobile Regional Tax Service) as an effort to bring services closer to the community and increase taxpayer compliance. The purpose of this study is to describe the service innovation of Lapak Darling (Mobile Regional Tax Service) in optimizing the collection of Land and Building Tax at the Regional Revenue Agency of Pekanbaru City using the theory of public service innovation according to Bloch which consists of four indicators, namely Product, Process, Organization, and Communication. This study uses a qualitative research method with a descriptive research type. Data collection techniques are carried out through interviews, observations, and documentation with informants. The results of the study indicate that the service innovation of Lapak Darling has been running well and has had a positive impact on optimizing the collection of Land and Building Tax in Pekanbaru City. The Lapak Darling service innovation is an effective innovative strategy in improving the quality of tax services and supporting the optimization of Land and Building Tax collection at the Pekanbaru City Regional Revenue Agency, especially through increasing accessibility, ease of service, and taxpayer compliance. This innovation is implemented through a proactive service approach by providing direct services to the community in strategic locations such as residential areas, sub-district offices, village offices, and public activities such as Car Free Day. The existence of Lapak Darling has proven to provide convenience for the community in making payments, registrations, and consultations on Land and Building Tax without having to come to the BAPENDA office. This has had a positive impact on increasing taxpayer participation and compliance, although the achievement of the overall Land and Building Tax revenue target still requires further strengthening through expanding service coverage and increasing the intensity of program implementation. Keywords: Public Service Innovation, Lapak Darling, Land and Building Tax